Biomimetic mineralization of metal–organic frameworks around polysaccharides. Issue 7 (9th January 2017) - Liang, Kang; Wang, Ru; Boutter, Manon; Doherty, Cara M.; Mulet, Xavier; Richardson, Joseph J.
Abstract : Biomimetic mineralization exploits natural biomineralization processes for the design and fabrication of synthetic functional materials. Abstract : Biomimetic mineralization exploits natural biomineralization processes for the design and fabrication of synthetic functional materials. Here, we report for the first time the use of carbohydrates (polysaccharides) for the biomimetic crystallization of metal–organic frameworks. This discovery greatly expands the potential and diversity of biomimetic approaches for the design, synthesis, and functionalization of new bio-metal–organic framework composite materials.